PENGEMBANGAN E-MODUL MATERI LIPID BERBASIS SCIENCE, TECHNOLOGY, ENGGINERING AND MATHEMATIC (STEM) - Dewi Handayani; Tiara Dia Amanda; Nurhamidah (University of Bengkulu, 2026)
This study aims to determine the level of feasibility of e-module, student respons to e-module, and average student learning outcomes. The development of this e-module uses a 4D model (define, design, develop, disseminate). The subjects of the study were 12 students of Chemistry Education semester VI (six) for small group trials and 21 students of Chemistry Education semester IV (four) for large group trials. The instruments used are interview sheets, needs questionnaires, validation sheets, respons questionnaires, pretest and posttest sheets. The results of product validation received a score of 84.8% which was included in the very valid criteria, and student responses were included in the very good criteria with a score of 90.4%. The results of the large group trial showed that there was an increase in student learning outcomes that were included in the medium category with an average N-Gain score of 0.52. The results of this study show that the use of STEM-based lipid material e-modules is proven to improve student learning outcomes. Keywords: E-Modul; STEM; Lipid; Hasil Belajar